BOSNIA AND CROATIA IN SOCIALIST FEDERAL REPUBLIC OF YUGOSLAVIA: INSTITUTIONAL PROBLEMS OF AN ETHNIC FEDERATION - О. G. Kharitonova (Сравнительная политика, 2015)
The article analyzes the disintegration of Yugoslav statehood focusing on institutional problems of ethnic federation. The author describes the main factors of the collapse of the Yugoslav Federation and the emergence of independent Bosnia and Croatia: economic inequality between republics, economic nationalism, the weakening of the center and the communist party fragmentation.